Access to Landscape Finance for Small-Scale Producers and Local Communities: A Literature Review - Louman, B.; Girolami, E.D.; Shames, S.; Primo, L.G.; Gitz, V.; Scherr, S.J.; Meybeck, A.; Brady, M.A. (MDPI, 2022)
Access to finance is a key element of sustainable and inclusive landscapes. We conducted a literature review to identify the factors that contribute to or hinder inclusive financing for micro/small/medium-sized enterprises and projects across sectors in ways that collectively contribute to more sustainable landscapes in the tropics. The key factors in the design of inclusive landscape finance are landscape governance, the financial literacy of local stakeholders, access to finance technology and services, and inclusive finance facilities and associated mechanisms for integrated (i.e., multi-project, multi-sector, spatially coordinated) landscape finance. The most frequent challenges are the types of existing financial products, the lack of livelihood assets among recipients (such as capital and income), the lack of transparency in finance mechanisms, the small scale of potential business cases, and the high risks perceived by finance providers and their customers. From this review, we propose components specifically focused on financial inclusion that complement the framework for integrated landscape finance developed by the Finance Solutions Design Team for the 1000 Landscapes for 1 Billion People Initiative. We suggest how the revised framework can be applied in designing and assessing the inclusiveness of finance mechanisms for integrated landscape management and to guide further research.